A Novel Method for Gaining New Insight on Flows Over Inundated Landscapes - Shailesh van derSteeg; Haiqing Xu; Raymond Torres; Edwin P. L. Elias; Jessica C. Sullivan; Enrica Viparelli; David Shelley; Venkataraman Lakshmi (Geophysical Research Letters)
Abstract We present a novel approach for detecting surface water flows over flooded terrain. The approach requires a minimum of three stage measurements and can be applied to any inundated surface, across a range of temporal and spatial scales. This method creates new and robust opportunities for field observation and for validation of numerical simulations and remote sensing analyses. In this proof‐of‐concept study, we found that floodplain free surface gradients were particularly variable during sub‐bankfull inundation, including abrupt current reversals. Also, flow direction varied with stage and the rate of change in stage. The “triangular facet” approach provides a new type of mesoscale insight of flow processes over inundated landscapes, highlighting flow complexity. Moreover, the approach provides information on floods that represent a compromise between point velocimeter measurements and satellite remote sensing and it can provide substantial benefits to society by aiding in flood hazard and mitigation assessment and planning.